Acute Onset Psychosis With Mystical Delusions in a Young Male Patient Following Discontinuation of Corticosteroid Therapy: A Case Report. Issue 5 (8th September 2022) - Bartolomei, Giuseppe; Lorenzini, Luca; Martelli, Maria; Gambaro, Eleonora; Zeppegno, Patrizia; Gramaglia, Carla
Abstract : Corticosteroid-based drugs are widely used in the general population to treat several acute and chronic inflammatory conditions. However, the therapeutic efficacy of these drugs is often accompanied by severe psychiatric adverse effects through a yet unknown mechanism. To further complicate this situation, therapeutic strategies to counteract psychotic symptoms associated with these agents have yet to be devised. We report a case of a young white male Jehovah's Witness admitted to the psychiatry ward of the Maggiore della Carità Hospital, Novara, Italy. At admission, the patient presented with psychomotor agitation, auditory hallucinations, and thought disturbances, resulting in the working diagnosis of a manic episode with psychotic features. During the 16 days of his hospital admission, the patient was treated with antipsychotic medications (aripiprazole and haloperidol) and with benzodiazepines (lorazepam), and he achieved a complete remission of all psychotic symptoms. While his psychiatric history was negative, his medical records revealed a recent discharge from the infectious disease ward with a diagnosis of infectious mononucleosis treated with intravenous betamethasone. Thus, at discharge, a diagnosis of steroid-induced psychosis was made. In conclusion, our findings are suggestive of a potential role played by corticosteroids in the development of psychotic symptoms, for which routine screening protocols and therapeutic guidelines are still lacking.